ЕРЗИЙЎАР ДӘСТАНЫНДАҒЫ ОБРАЗЛАР - Бекбергенова, А.У. (FAN va JAMIYAT, 2022)
The article deals with the system of images in the epic "Erziyuar" in the repertoire of Kurbanbai zhyrau. Detailed investigation elicit a fact that the obtained examples from vary jirau variants made the work much more significant.